2021
DOI: 10.1038/s41598-021-91925-6
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of antibacterial and antiviral perhydrolase-polydopamine composite coatings

Abstract: In situ generation of antibacterial and antiviral agents by harnessing the catalytic activity of enzymes on surfaces provides an effective eco-friendly approach for disinfection. The perhydrolase (AcT) from Mycobacterium smegmatis catalyzes the perhydrolysis of acetate esters to generate the potent disinfectant, peracetic acid (PAA). In the presence of AcT and its two substrates, propylene glycol diacetate and H2O2, sufficient and continuous PAA is generated over an extended time to kill a wide range of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It has been reported that the lentivirus-encoding GFP can be used as a virus model, and GFP expression has been detected via fluorescence imaging analysis up to 3 days after infection. , Compared to the lentivirus-based assay, SeV-derived luciferase expression could be detected even 16 h after infection (Figure S2). Additionally, we observed that the luciferase-based assay system gave rise to a superior signal/noise ratio compared to the GFP-based assay (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the lentivirus-encoding GFP can be used as a virus model, and GFP expression has been detected via fluorescence imaging analysis up to 3 days after infection. , Compared to the lentivirus-based assay, SeV-derived luciferase expression could be detected even 16 h after infection (Figure S2). Additionally, we observed that the luciferase-based assay system gave rise to a superior signal/noise ratio compared to the GFP-based assay (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent AcT–PDA coatings drastically reduced the infectivity of a SARS-CoV-2 pseudovirus within minutes. 67 A poly(dimethyl amino methyl) styrene- co -1 H ,1 H ,2 H ,2 H -perfluorodecyl acrylate (PDP) coating on polyester fabric exhibited excellent antiviral activity against lentivirus-EGFP and satisfactory biocompatibility with NIH 3T3 fibroblast cells from mice. 68 The positive zeta potential value of PDP-coated textiles (+23.2 ± 0.2 mV) can electrostatically interact with negatively charged bacteria and viruses, and subsequently rupture the microbial structure, resulting in microbial inactivation.…”
Section: Nanostructured Antiviral Coatingsmentioning
confidence: 99%
“…In this regard, other biotechnological developments in the current pandemic context have implemented similar strategies to evaluate the antiviral properties of biomaterials. [25][26][27] Since the main media where the antiviral activity was tested was the surface of face masks, we propose that implementing this kind of sprayable product would allow the face masks to be reused without the need of sterilization or their elimination after use. Therefore, the two major advantages attributable to CH@Ag/CuO NPs spray formulations are the prevention of the spread of viruses, including SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of these viruses for this study is based on the requirement of laboratories with high biosecurity levels for the manipulation of SARS‐CoV‐2 to guarantee the personal biosafety. In this regard, other biotechnological developments in the current pandemic context have implemented similar strategies to evaluate the antiviral properties of biomaterials [25–27] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation